A Model to Monitor Rational Use of Antibiotics in Chiang Yuen Hospital, Mahasarakham Province - Pothidorkmai, Yordporn (Journal of Health Science of Thailand, 2017)
This study was a quasi-experimental research aiming at developing a model to reduce the use of antibiotics for the treatment of two groups of diseases - acute gastroenteritis (AGE) and upper respiratory tract infection (URTI). Ten physicians in Chiang Yuen Hospital, Mahasarakham province participated the process; and the study tools included (1) medication history from the treatment databases (HosXP), and (2) electronic reports of antibiotics prescriptions generated from Microsoft Excel based on the E-Tool software of the National Health Security Office. The rational drug use intervention model included a series of activities ranging from rational use of drug policy directive, workshops on proper use of antibiotics, focus group discussions, individual physician warnings during writing prescription, close monitoring and feedback mechanism, the use of Facebook and Line group, poster display in treatment rooms, and letters to each physician. The antibiotic prescription rates for the 2 disease groups were compared between the period from April to September 2014 and October 2014 to March 2015 when the interventions for rational use of drugs was in place. It was found that after the model implementation, the antibiotics prescriptions for acute gastroenteritis reduced from 51.2% to 33.0%, and for upper respiratory tract infections from 43.9% to 28.0%. The overall cost of antibiotics for the two disease groups decreased from 661,956.41 baht to 501,010.74 baht. It should be concluded that the model had produced favorable outcomes in the control of overuse of antibiotics.